Α-Glucosidase and α-amylase inhibitory constituents of Tinospora crispa: Isolation and chemical profile confirmation by ultra-high performance liquid chromatography-quadrupole time-of-flight/mass spectrometry. (June 2015) - Hamid, H.A.; Yusoff, M.M.; Liu, M.; Karim, M.R.
Highlights: This study reports the isolation of eleven pure compounds from Tinospora crispa . α-Glucosidase and α-amylase enzyme inhibition by the compounds was evaluated. The relationship between the enzyme inhibition and structure was evaluated. UPLC-QToF was used for separation and identification of compounds. Abstract: Tinospora crispa has been used in Malaysia to treat diabetes mellitus. We evaluated the effects of compounds isolated from T. crispa vines on the starch digestive enzymes, α-glucosidase and α-amylase. Borapetoside C was the most potent α-glucosidase inhibitor (IC50 = 0.0527 ± 0.008 mg/ml), followed by 4-hydroxy benzaldehyde (IC50 = 0.557 ± 0.004 mg/ml), and the alkaloids lysicamine and liriodenine (IC50 = 0.562 ± 0.003 mg/ml). Borapetoside C also potently inhibited α-amylase inhibitory activity (IC50 = 0.775 ± 0.005 mg/ml). The relationship between compound activity and content in the extracts was determined by ultra-high performance liquid chromatography-quadrupole time-of-flight/mass spectrometry (UPLC-QToF/MS). These results suggest that borapetoside C is the main primary active component of T. crispa extracts, mediating α-glucosidase and α-amylase inhibition.